Non-invasive Liver Fibrosis Scores Are Associated With Recurrence of Postoperative Chronic Subdural Hematoma - Zhang, Peng; Wang, Hua; Bao, Han; Wang, Ning; Chen, Zhen; Tu, Qi; Lin, Xiao; Li, Yun; Zheng, Zezheng; Chen, Yu; Ruan, Linhui; Zhuge, Qichuan (Frontiers in Neurology, 2022)
Objective Although liver diseases have already been identified as a risk factor for increased recurrence and mortality in patients with chronic subdural hematoma (CSDH), the association between subclinical liver disease, specifically liver fibrosis (LF), and CSDH remains unknown. In the present study, we aimed to investigate the association between the LF scores and CSDH recurrence. Methods We retrospectively analyzed consecutive patients with CSDH who underwent burr-hole irrigation in the First Affiliated Hospital of Wenzhou Medical University between January 2015 and December 2018. The clinical data were collected, and the LF scores were calculated including aspartate aminotransferase–platelet ratio index (APRI), fibrosis-4 (FIB-4), and Forns index. Multivariable logistic regression analysis was applied to identify the association between the LF scores and CSDH recurrence, and Cox regression model and Fine–Gray competing risks model were performed to calculate hazard ratios (HRs) for CSDH recurrence based on time-to-event outcomes. The C-statistic, the integrated discrimination improvement (IDI), and the net reclassification improvement (NRI) evaluated the additive value of the LF scores to predict the recurrence of CSDH. Results A total of 419 patients with CSDH were included, hematoma recurrence was observed in 62 patients (14.80%) within 1 year after surgery. The LF scores were significantly higher in those who recurred, whereas the standard hepatic assays were mostly normal. The patients were assigned to groups of high and low LF scores based on the validated cut-offs; compared with the subjects with low scores, those with high score levels had significantly higher recurrence rates. After adjusting for potential confounders, the LF scores were independently associated with CSDH recurrence, multivariable-adjusted HRs (95% CI) for those with higher levels of APRI, FIB-4, and Forns score were 4.32 (1.37–13.60), 2.56 (1.20–5.43), and 2.02 (1.07–3.79) for the recurrence of CSDH, respectively. Moreover, adding the APRI to the conventional model improved the C-statistic from 0.731 to 0.763, with an NRI and IDI of 7.50 and 1.35%, respectively. Two further commonly-used LF score indices (FIB-4 score and Forns index) yielded comparable results. Conclusions The data from this study first indicated that the high LF scores were significantly associated with the recurrence of CSDH and that careful follow-up in these patients may be needed.